The Effect of Tax Socialization, Tax Understanding, and Service Quality on Taxpayer Compliance : A Study on Individual Taxpayers at KPP Pratama Gianyar - I Gusti Ngurah Febriana Putra; Ni Luh Supadmi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Taxpayer compliance represents citizens’ awareness and responsibility in fulfilling their tax obligations to support national revenue. This study aims to analyze the influence of tax socialization, tax understanding, and service quality on individual taxpayer compliance at KPP Pratama Gianyar. Using a quantitative research approach, data were collected through a questionnaire survey distributed to 100 individual taxpayers registered at the tax office. The collected data were analyzed using multiple linear regression to determine the simultaneous and partial effects of the three independent variables. The research findings reveal that tax socialization, tax understanding, and service quality each have a positive and significant influence on taxpayer compliance. These results indicate that effective tax socialization enhances taxpayer awareness, comprehensive understanding increases compliance accuracy, and high-quality services strengthen taxpayers’ willingness to fulfill their tax duties. Therefore, improving these three aspects can significantly enhance compliance levels, which in turn contributes to the optimization of tax revenue and the strengthening of the national fiscal system.